Determinants of stock price and company value viewed from corporate governance, leverage, profitability, EPS - Hutabarat, Francis (Institute of Computer Science (IOCS), 2024)
For the purpose of this study, the stock price and firm value of banks, as well as factors such as Corporate Governance, Leverage, Profitability, and Earnings Per Share (EPS), which have the potential to influence them, will be investigated. This research makes use of a sample size of fifteen banks, and the secondary data is derived from the financial statements of banking sector businesses that are listed on the infobank15 index throughout the period of 2018-2020. The total sample size here is forty-five. Both descriptive analysis and linear regression, as well as significant tests, are utilized in this work. According to the findings of this research, corporate governance, leverage, profitability, and earnings per share (EPS) each have a considerable impact on stock price and company value, respectively, in a partial and simultaneous manner